Certainty and Subjectivity in English Education Research: A Cross Cultural Systemic Functional Analysis - Alramadan, May Mahdi (Universitas Pendidikan Mandalika, 2022)
This study examines the use of epistemic modality (expressions that signal varying degrees of certainty and subjectivity) by writers of English education research. Epistemic modality is a crucial, yet intricate, rhetorical device through which writers qualify their claims and construct a stance towards their texts and readers. Disciplinary and cultural norms influence the rhetorical use of modality in academic texts. To understand the impact of these contextual factors, linguistic descriptions need to examine discourse produced in individual disciplines and even subdisciplines. Using an exploratory comparative approach, the present study analyzes education research that is produced by native-English-speaking and EFL Arab writers: (1) to describe the discipline-specific practices that are adopted by native writers to manipulate the degrees of certainty and subjectivity in their discourse; and (2) to explore how these practices vary cross-culturally. Sixty research papers are analyzed using the finely grained model of Systemic Functional Linguistics. The findings show a disciplinary preference whereby native writers avoided expressing hesitancy and doubt and preferred a moderately confident epistemic stance to create convincing arguments. These writers’ epistemic style was also objective and detached. The EFL texts, in contrast, were less dialogic and had higher levels of confidence, explicitness, and subjectivity. Although advanced in their linguistic and disciplinary proficiency, the non-native writers displayed some patterns that are generally characteristic of other Arab and non-Arab L2 writers/learners, indicating the vital role that culture and nativeness play in rhetorical strategy use. The paper ends by highlighting the need for explicit instruction of epistemic modality in Arab higher education institutions in order for non-native writers to produce academic texts that are persuasively effective from the perspective of the international academic community.